PENEGAKAN HUKUM PENGEBORAN MINYAK ILEGAL PADA PERTAMBANGAN RAKYAT: Law Enforcement Of Illegal Oil Drilling In Public Mining - Nuril Firdausiah (Constitution Journal, 2022)
Natural resources, in the form o;f minerals and coal contained in the earth of indonesia are one of the capital controlled by the state to achieve public welfare. One of the controls has been regulated in law number 3 of 2020 concerning amendments to law number 4 of 2009 concerning mineral and col mining. Traditional oil mining activities are part of the utilization of natural resources which are expected to provide welfare for the village community. Illegal oil drilling activities carried out traditionally seem to be an endless story, which occurs due to lack of attention to being able to manage old wells. Actually, the management of old wells has been regulated through ministerial regulation and mineral resources number i of 2008 concerning guidelines for controlling petroleum mining in old wells. But what is happening now is that there are many levels of illegal oil drilling carried out traditionally, such as using used pipes, which are then pumped or drilled to extract crude oil, which is plugged into the ground and then pulled out using a diesel engine driven by a foot clutch and then collected. 500 liter tanks. Judging from the drilling process, there are many impacts that will arise due to illegal drilling of crude oil, including fires and exploding wells that cannot be managed properly by the perpetrators, therefore there must be regulations issued by the goverment. Keywords: Illegal Oil, Drilling, Mining, Regulation. Sumber daya alam, berupa mineral dan batubara yang terkandung didalam bumi indonesia merupakan salah satu modal yang dikuasai negara untuk mencapai kesejahteraan masyarakat. Salah satu penguasaannya yang telah diatur dalam Undang-Undang Nomor 3 Tahun 2020 tentang Perubahan Atas Undang-Undang Nomor 4 Tahun 2009 tentang Pertambangan Mineral dan Batubara. Aktifitas penambangan minyak tradisional adalah bagian dari pemanfaatan sumber daya alam yang diharapkan mampu memberikan kesejahteraan bagi masyarakat desa. Kegiatan pengeboran minyak ilegal yang dilakukan secara tradisional seakan menjadi cerita yang tak berkesuduhan, yang mana terjadi karena kurangnya pengawasan oleh pemerintah dan kurangnya perhatian untuk dapat mengelola sumur tua. Sebenarnya pengelolaan sumur tua sudah diatur melalui Peraturan Menteri dan Sumber Daya Mineral Nomor 1 Tahun 2008 Tentang Pedoman Penguasaan Pertambangan Minyak Bumi pada Sumur Tua. Namun yang terjadi saat ini adalah banyaknya tingkat pengeboran minyak ilegal yang dilakukan secara tradisional seperti menggunakan pipa-pipa bekas, yang kemudian pengambilan minyak mentahnya dipompa atau semacam di bor, yang ditancapkan kebawah tanah kemudian ditarik dengan mengguunakan mesin diesel yang digerakkan dengan kopling kaki lalu dikumpulkan ditangki-tangki berukuran 500 liter. Dilihat dari proses pengeborannya, banyak sekali dampak yang akan timbul akibat pengelolaan minyak bumi secara ilegal drilling di antaranya yang terjadi kebakaran dan meledaknya sumur-sumur yang tidak dapat dikelola dengan baik oleh pelaku, oleh karena itu harus ada regulasi yang dikeluarkan oleh pemerintah. Kata Kunci : Minyak Ilegal, Pengeboran, Pertambangan, Regulasi.